2009
DOI: 10.1002/eji.200838726
|View full text |Cite
|
Sign up to set email alerts
|

A novel IL‐17‐dependent mechanism of cross protection: Respiratory infection with mycoplasma protects against a secondary listeria infection

Abstract: Immune responses to pathogens occur within the context of current and previous infections. Cross protection refers to the phenomena where infection with a particular pathogen provides enhanced resistance to a subsequent unrelated pathogen in an antigen-independent manner. Proposed mechanisms of antigen-independent cross protection have involved the secretion of IFN-c, which activates macrophages, thus providing enhanced innate immunity against the secondary viral or bacterial pathogen. Here we provide evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 52 publications
1
33
0
Order By: Relevance
“…in 30). More recently, the involvement of Th17/IL-17 in protective immunity against intracellular bacterial infections was also reported (31)(32)(33)(34). In particular, we and others reported that IL-17 is important in host defense against chlamydial lung infection (31,34).…”
Section: Enhanced Inducible Costimulator Ligand (Icos-l) Expression Osupporting
confidence: 61%
“…in 30). More recently, the involvement of Th17/IL-17 in protective immunity against intracellular bacterial infections was also reported (31)(32)(33)(34). In particular, we and others reported that IL-17 is important in host defense against chlamydial lung infection (31,34).…”
Section: Enhanced Inducible Costimulator Ligand (Icos-l) Expression Osupporting
confidence: 61%
“…This includes, but is not limited to, models of Mycobacterium tuberculosis (45), Salmonella (46), and Listeria monocytogenes infection in which IL-17 deficiency is associated with an enhanced inflammatory response (47) and substantial neutrophil-mediated tissue pathology (48). Contrary to the data we have presented in this study, IL-17 was proinflammatory in nature in these infections, and a deficiency in IL-17 resulted in higher pathogen burdens, stemming from uncontrolled pathogen growth.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it is generally thought that IL-17/Th17 responses have limited role in intracellular bacterial infections mainly based on the theoretical insufficiency of neutrophils in killing intracellular bacteria. Indeed, IL-17 gene knockout (KO) 3 and IL-17R KO mice are not more susceptible to primary Mycobacterium tuberculosis and Listeria monocytogenes infections than wild-type mice (17)(18)(19). However, the involvement of IL-17 in host defense against M. tuberculosis was also reported, especially in inducing recall response following vaccination (20,21).…”
mentioning
confidence: 99%